Portulaca oleracea L. extracts alleviate 2,4-dinitrochlorobenzene-induced atopic dermatitis in mice - Lv, Wei-jie; Huang, Jie-yi; Li, Shu-peng; Gong, Xiao-pei; Sun, Jing-bo; Mao, Wei; Guo, Shi-ning (Frontiers in Nutrition, 2022)
Atopic dermatitis (AD) is a common chronic allergic skin disease characterized clinically by severe skin lesions and pruritus. Portulaca oleracea L. (PO) is a resourceful plant with homologous properties in medicine and food. In this study, we used two different methods to extract PO, and compared the therapeutic effects of PO aqueous extract (POAE) and PO ultrasound-assisted ethanol extract (POEE) on 2,4-dinitrochlorobenzene (DNCB)-induced AD mice. The results showed that in POAE and POEE, the extraction rates of polysaccharides were 16.95% and 9.85%, while the extraction rates of total flavonoids were 3.15% and 3.25%, respectively. Compared with AD mice, clinical symptoms such as erythema, edema, dryness and ulceration in the back and left ear were alleviated, and pruritus behavior was reduced after POAE and POEE treatments. The thickness of the skin epidermis was thinned, the density of skin nerve fibers labeled with protein gene product 9.5 (PGP9.5) was decreased, and mast cell infiltration was reduced. There was a decrease in blood lymphocytes, eosinophils and basophils, a significant decrease in spleen index and a noticeable decrease in serum immunoglobulin E (Ig E). POEE significantly reduced the concentration of the skin pruritic factor interleukin (Il)-31. POAE and POEE reduced the concentration of skin histamine (His) and down-regulated the mRNA expression levels of interferon-gamma (Ifn-γ), tumor necrosis factor-α (Tnf-α), thymic stromal lymphopoietin (Tslp), and Il-4 in skin lesions. These results suggested that POAE and POEE may inhibit atopic response and alleviate the clinical symptoms of AD by inhibiting the expression of immune cells, inflammatory mediators and cytokines. PO may be a potential effective drug for AD-like diseases.